Community perceived barriers to uptake of health services among men at Sedibeng district in South Africa - Ndumiso Tshuma; Daniel N. Elakpa; Clinton Moyo; Tshepo M. Ndhlovu; Mathildah M. Mokgatle; Sangiwe Moyo; Sehlule Moyo; Martha Chadyiwa; Mandeep K. Kochar; Mokgadi Malahlela; Takalani G. Tshitangano; David D. Mphuthi (AOSIS, 2024)
Background: This qualitative study aimed to investigate the barriers that hinder men's utilisation of healthcare services in the Sedibeng district of South Africa. Methods: The study was conducted using flyers with questions posted on the Best Health Solutions' Facebook page for two weeks. A convenience sampling method was used and a total of 104 comments were collected from 64 respondents. The authors analysed the participants' self-reported data thematically on demographics, geographic area, and reasons for men not using healthcare services. Results: The findings revealed that sociocultural norms played a significant role in men's reluctance to seek medical help, as it was perceived as a sign of weakness. The scarcity of male healthcare professionals hinders open discussions. Stigma and discrimination were identified as substantial barriers. Convenience, trust, and confidentiality concerns, along with the influence of intimate partners, also influence men's decision-making. Conclusion: This study highlights the complex interplay between various barriers that impact men's utilisation of healthcare services in the district. By addressing these factors, healthcare providers and policymakers can enhance healthcare access and promote better health outcomes for men in Sedibeng district. Contribution: The manuscript's primary contribution lies in uncovering multifaceted barriers to men's healthcare utilisation in Sedibeng district. It explores socio-cultural norms, healthcare worker demographics, stigma, discrimination, convenience factors, trust, confidentiality concerns, and the influence of intimate partners on men's healthcare choices. These insights illuminate the complex factors affecting men's healthcare access, providing valuable knowledge for healthcare providers and policymakers.